Systemic and adipocyte transcriptional and metabolic dysregulation in idiopathic intracranial hypertension - Westgate, Connar S.J.; Botfield, Hannah F.; Alimajstorovic, Zerin; Yiangou, Andreas; Walsh, Mark; Smith, Gabrielle; Singhal, Rishi; Mitchell, James L.; Grech, Olivia; Markey, Keira A.; Hebenstreit, Daniel; Tennant, Daniel A.; et al. (JCI insight, 2021)
BACKGROUNDIdiopathic intracranial hypertension (IIH) is a condition predominantly affecting obese women of reproductive age. Recent evidence suggests that IIH is a disease of metabolic dysregulation, androgen excess, and an increased risk of cardiovascular morbidity. Here we evaluate systemic and adipose specific metabolic determinants of the IIH phenotype.METHODSIn fasted, matched IIH (n = 97) and control (n = 43) patients, we assessed glucose and insulin homeostasis and leptin levels. Body composition was assessed along with an interrogation of adipose tissue function via nuclear magnetic resonance metabolomics and RNA sequencing in paired omental and subcutaneous biopsies in a case-control study.RESULTSWe demonstrate an insulin- and leptin-resistant phenotype in IIH in excess of that driven by obesity. Adiposity in IIH is preferentially centripetal and is associated with increased disease activity and insulin resistance. IIH adipocytes appear transcriptionally and metabolically primed toward depot-specific lipogenesis.CONCLUSIONThese data show that IIH is a metabolic disorder in which adipose tissue dysfunction is a feature of the disease. Managing IIH as a metabolic disease could reduce disease morbidity and improve cardiovascular outcomes.FUNDINGThis study was supported by the UK NIHR (NIHR-CS-011-028), the UK Medical Research Council (MR/K015184/1), Diabetes UK, Wellcome Trust (104612/Z/14/Z), the Sir Jules Thorn Award, and the Midlands Neuroscience Teaching and Research Fund.